Porphyrin-rylene-diimide-hexabenzocoronene triads - Martin, Max; Dusold, Carolin; Hirsch, Andreas; Jux, Norbert (Journal of Porphyrins and Phthalocyanines, 2020)
Hexa-peri-hexabenzocoronenes (HBCs), substituted by two different chromophores in an ortho arrangement, were synthesized for the first time and investigated towards their photophysical properties. Rylene-diimide dyes, in particular naphthalene-diimides (NDIs) and perylene-diimides (PDIs), were attached to the HBC as the first, and porphyrins as the second chromophore. Therefore, porphyrin-NDI-HPB as well as porphyrin-PDI-HPB precursors were accessed and converted into the respective HBC derivatives applying oxidative Scholl conditions. UV-vis absorption and fluorescence emission spectroscopy showed interesting photophysical behavior such as energy transfer processes. Particularly, the porphyrin-PDI-HBC displays pronounced absorption features between 330-650 nm, which cover a wide range of the visible spectrum.
CRIS-Team Scopus Importer:2019-08-23
Keywords: hexabenzocoronene; nanographene; naphthalene; perylene; porphyrin; rylene-diimide